Porosity gradients as a means of driving lateral flows at cometary surfaces. (January 2020) - Christou, Chariton; Dadzie, S. Kokou; Marschall, Raphael; Thomas, Nicolas
Abstract: The Rosetta spacecraft has provided invaluable and unexpected information about cometary outgassing. The on-board instruments ROSINA, MIRO, and VIRTIS showed non-uniform outgassing of H2 O over the surface of the nucleus. Rarefied gas flows display remarkable flow phenomena that may help explain diverse physical observations and models have been used in various engineering applications. Typical examples are flows generated by temperature variations such as thermal creeping flows that may have applications in cometary research. In this paper, we demonstrate how porosity variations in a porous medium combined with rarefaction can also lead to high tangential speed flow at a surface. Outgassing through a porous surface layer has been postulated as one possible mechanism at the cometary surfaces. We use the Direct Simulation Monte Carlo (DSMC) method to investigate such flows. The porous media structure consists of micro computed tomography (micro-CT) image of real Earth rock samples with high resolution. We show that lateral gas density gradients can be produced in a straightforward manner leading to substantial non-radial flow. Highlights: Lateral porosity gradient can generate steep lateral pressure gradient leading to potentially high speed lateral flows. Porosity variations may be responsible for high speed lateral flows which may be responsible for substantial grain transports. A structure with varying porosity could also contribute to the observed coma inhomogeneities. Coma might have an additional non-time-dependent component which is related to lateral porosity gradients.